The impacts of alien species on river bioassessment - Maria João Feio; Janine P. da Silva; Robert M. Hughes; Francisca C. Aguiar; Carlos B.M. Alves; Sebastian Birk; Marcos Callisto; Marden S. Linares; Diego R. Macedo; Paulo S. Pompeu; Wayne Robinson; Christian Schürings; et al. (Journal of Environmental Management, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Fish and macroinvertebrate assemblages reveal extensive degradation of the world's rivers - Maria João Feio; Robert M. Hughes; Sónia R. Q. Serra; Susan J. Nichols; Ben J. Kefford; Mark Lintermans; Wayne Robinson; Oghenekaro N. Odume; Marcos Callisto; Diego R. Macedo; Jon S. Harding; Adam G. Yates; et al. (Global Change Biology, 2023)
Rivers suffer from multiple stressors acting simultaneously on their biota, but the consequences are poorly quantified at the global scale. We evaluated the biological condition of rivers globally, including the largest proportion of countries from the Global South published to date. We gathered macroinvertebrate‐ and fish‐based assessments from 72,275 and 37,676 sites, respectively, from 64 study regions across six continents and 45 nations. Because assessments were based on differing methods, different systems were consolidated into a 3‐class system: Good, Impaired, or Severely Impaired, following common guidelines. The proportion of sites in each class by study area was calculated and each region was assigned a Köppen‐Geiger climate type, Human Footprint score (addressing landscape alterations), Human Development Index (HDI) score (addressing social welfare), % rivers with good ambient water quality, % protected freshwater key biodiversity areas; and % of forest area net change rate. We found that 50% of macroinvertebrate sites and 42% of fish sites were in Good condition, whereas 21% and 29% were Severely Impaired, respectively. The poorest biological conditions occurred in Arid and Equatorial climates and the best conditions occurred in Snow climates. Severely Impaired conditions were associated (Pearson correlation coefficient) with higher HDI scores, poorer physico‐chemical water quality, and lower proportions of protected freshwater areas. Good biological conditions were associated with good water quality and increased forested areas. It is essential to implement statutory bioassessment programs in Asian, African, and South American countries, and continue them in Oceania, Europe, and North America. There is a need to invest in assessments based on fish, as there is less information globally and fish were strong indicators of degradation. Our study highlights a need to increase the extent and number of protected river catchments, preserve and restore natural forested areas in the catchments, treat wastewater discharges, and improve river connectivity.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Characterisation of Sweet potato collusive virus (SPCV) isolates from sweet potato (Ipomea batatas) in Australia - Amit C. Sukal; Sandra Dennien; Dawit B. Kidanemariam; Karlah Norkunas; Eric Coleman; Robert M. Harding; Anthony P. James (Australasian Plant Pathology, 2022)
Sweet potato collusive virus (SPCV) is a member of the genus Cavemovirus , family Caulimoviridae , for which only one full-length genome sequence has been reported. SPCV was first detected in Australia in 2007 in two sweet potato accessions using the nitrocellulose membrane ELISA kit developed by the International Potato Centre (CIP). Infected plants were also shown to contain isometric virions of ~ 50 nm, typical of members of the genera Cavemovirus , Caulimovirus , Petuvirus and Soymovirus . We have now sequenced and characterised the complete genomes of the two SPCV isolates (designated SPCV-Aus1 and -Aus2) using a combination of next-generation sequencing and PCR/Sanger sequencing. The sequences of both isolates encode three major ORFs with a genome organisation typical of cavemoviruses. However, isolate SPCV-Aus2 possesses a considerably shorter genome length of 7275 bp compared to SPCV-Aus1 (7712 bp) and the only available full-length sequence from a Portuguese isolate (7723 bp; GenBank accession number NC_015328). Further, ORF 1 of SPCV-Aus2 is considerably shorter than the ORF 1 length of both SPCV-Aus1 and SPCV-Mad1. Phylogenetic and PASC analysis showed that SPCV-Aus1 is closely related to SPCV isolates from North and Central America, whereas SPCV-Aus2 clustered together with isolates from Portugal and Africa.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

Tert-butyldimethylsilyl chitosan synthesis and characterization by analytical ultracentrifugation, for archaeological wood conservation - Jennifer M. K. Wakefield; Susan Braovac; Hartmut Kutzke; Robert A. Stockman; Stephen E. Harding (European Biophysics Journal, 2020)
The Oseberg ship is one of the most important archaeological testimonies of the Vikings. After excavation in 1904, the wooden gravegoods were conserved using alum salts. This resulted in extreme degradation of a number of the objects a hundred years later through acid depolymerisation of cellulose and lignin. The fragile condition of the artefacts requires a reconsolidation which has to be done avoiding water as solvent. We synthesized tert- butyldimethylsilyl (TBDMS) chitosan which is soluble in a 50:50 solution of ethyl acetate and toluene. Measurement of its molecular weight, to anticipate its penetration, provided a challenge as the density difference of the polymer and solvent was too small to provide adequate solute redistribution under a centrifugal field, so a two-stage process was implemented (i) determination of the weight-average molar mass of the aqueous soluble activated precursor, chitosan mesylate, M w,mc using sedimentation equilibrium with the SEDFIT-MSTAR algorithm, and determination of the degree of polymerisation DP ; (ii) measurement of the average degree of substitution DS TBDMS of the TBDMS group on each chitosan monosaccharide monomer unit using NMR, to augment the M w,mc value to give the molar mass of the TBDMS-chitosan. For the preparation, we find M w = 9.8 kg·mol −1 , which is within the acceptable limit for penetration and consolidation of degraded wood. Future work will test this on archaeological wood from different sources.

Aminoethyl substitution enhances the self-assembly properties of an aminocellulose as a potential archaeological wood consolidant - Jennifer M. K. Wakefield; Robert Hampe; Richard B. Gillis; Agnes Sitterli; Gary G. Adams; Hartmut Kutzke; Thomas Heinze; Stephen E. Harding (European Biophysics Journal, 2020)
The 6-deoxy-6-aminocelluloses—or “aminocelluloses”—are a class of synthetic natural cellulose derivatives which are mostly aqueous soluble and have excellent film-forming properties. Recent studies have connected these properties at the molecular level with protein-like self-associative behaviour for a range of aminocelluloses including a 6-deoxy-6-(ω-aminoethyl) aminocellulose AEA-1 with the association being a two-stage process—a reversible oligomerisation followed by further (semi-reversible) aggregation into larger structures. Here, we synthesise and compare a new 6-deoxy-6-(ω-aminoethyl) aminocellulose AEA-1′ with different degree of substitution with one with further alkyl derivatisation, namely 6-deoxy-6-(ω-hydroxyethyl) aminocellulose HEA-1′. As with AEA-1, sedimentation velocity and sedimentation equilibrium in the analytical ultracentrifuge still show a two-stage process for both AEA-1′ and HEA-1′, with the latter giving higher molar masses. The consequences of these properties for use as consolidants for archaeological wood are considered.

Characterisation of a subgroup IB isolate of Cucumber mosaic virus from Xanthosoma sp. in sub-Saharan Africa - Dawit B. Kidanemariam; Amit C. Sukal; Adane D. Abraham; Joyce N. Njuguna; Benard O. Mware; Francesca Stomeo; James L. Dale; Anthony P. James; Robert M. Harding (Australasian Plant Pathology, 2019)

Molecular characterisation of a putative new polerovirus infecting pumpkin (Cucurbita pepo) in Kenya - Dawit B. Kidanemariam; Amit C. Sukal; Adane D. Abraham; Joyce N. Njuguna; Francesca Stomeo; James L. Dale; Robert M. Harding; Anthony P. James (Archives of Virology, 2019)

Characterization of an Australian isolate of taro bacilliform virus and development of an infectious clone - Dawit B. Kidanemariam; Amit C. Sukal; Kathy Crew; Grahame V. H. Jackson; Adane D. Abraham; James L. Dale; Robert M. Harding; Anthony P. James (Archives of Virology, 2018)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Erratum to: Complete genome sequence of Colocasia bobone disease-associated virus, a putative cytorhabdovirus infecting taro - Colleen M. Higgins; Nicolas Bejerman; Ming Li; Anthony P. James; Ralf G. Dietzgen; Michael N. Pearson; Peter A. Revill; Robert M. Harding (Archives of Virology, 2016)

Complete genome sequence of a novel zantedeschia mild mosaic virus isolate: the first report from Australia and from Alocasia sp. - Dawit B. Kidanemariam; Adane D. Abraham; Amit C. Sukal; Timothy A. Holton; James L. Dale; Anthony P. James; Robert M. Harding (Archives of Virology, 2016)

Complete genome sequence of Colocasia bobone disease-associated virus, a putative cytorhabdovirus infecting taro - Colleen M. Higgins; Nicolas Bejerman; Ming Li; Anthony P. James; Ralf G. Dietzgen; Michael N. Pearson; Peter A. Revill; Robert M. Harding (Archives of Virology, 2016)

Stream biomonitoring using macroinvertebrates around the globe: a comparison of large-scale programs - Daniel F. Buss; Daren M. Carlisle; Tae-Soo Chon; Joseph Culp; Jon S. Harding; Hanneke E. Keizer-Vlek; Wayne A. Robinson; Stephanie Strachan; Christa Thirion; Robert M. Hughes (Environmental Monitoring and Assessment, 2015)

Initiation of embryogenic cell suspensions of taro (Colocasia esculenta var. esculenta) and plant regeneration - Pradeep C. Deo; Mary Taylor; Robert M. Harding; Anand P. Tyagi; Douglas K. Becker (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Somatic embryogenesis, organogenesis and plant regeneration in taro (Colocasia esculenta var. esculenta) - Pradeep C. Deo; Robert M. Harding; Mary Taylor; Anand P. Tyagi; Douglas K. Becker (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

Molecular Analysis of Fiji Disease Virus Segments 2, 4 and 7 Completes the Genome Sequence - Robert M. Harding; Parichart Burns; Robert J. Geijskes; Richard M. McQualter; James L. Dale; Grant R. Smith (Virus Genes, 2006)

Molecular Analysis of Fiji Disease Fijivirus Genome Segments 1 and 3 - Richard B. McQualter; Grant R. Smith; James L. Dale; Robert M. Harding (Virus Genes, 2003)

Minisatellite mutational processes reduce F st estimates - J. Flint; J. Bond; D. C. Rees; A. J. Boyce; J. M. Roberts-Thomson; L. Excoffier; J. B. Clegg; M. A. Beaumont; R. A. Nichols; R. M. Harding (Human Genetics, 1999)

Minisatellite mutational processes reduce Fst estimates - J. Flint; J. Bond; D. C. Rees; A. J. Boyce; J. M. Roberts-Thomson; L. Excoffier; J. B. Clegg; M. A. Beaumont; R. A. Nichols; R. M. Harding (Human Genetics, 1999)

Incompatible pathogen infection results in enhanced reactive oxygen and cell death responses in transgenic tobacco expressing a hyperactive mutant calmodulin - Scott A. Harding; Daniel M. Roberts (Planta, 1998)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Characterization of 12 microsatellite loci of the human MHC in a panel of reference cell lines - Maureen P. Martin; Anita Harding; Robert Chadwwick; Mel Kronick; Michael Cullen; Ling Lin; Emmanuel Mignot; M. Carrington (Immunogenetics, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Characterization of 12 microsatellite loci of the human MHC in a panel of reference cell lines - Maureen P. Martin; Anita Harding; Robert Chadwick; Mel Kronick; Michael Cullen; Ling Lin; Emmanuel Mignot; M. Carrington (Immunogenetics, 1997)